KOMPOSISI MUSIK ARABIAN - Andry Pradana; Yensharti Yensharti; Yos Sudarman (FBS Universitas Negeri Padang, 2013)
Abstract Arabian Music Composition was inspired based on (1) harmonic minor note and zygana minor note that has been developed become an Art Project (2) want this composition become an ensamble form, (3) using western instrument which describe the happening of arabian. Kata kunci : Komposisi, Arabian, Ensembel.